The treasure - Shulevitz, Uri, 1935- ([New York] : Farrar, Straus, and Giroux, 1986)
A retelling of the traditional English tale in which a poor man follows the advice of his dream and is eventually led to a treasure.
"A Sunburst book.".
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Book Links (A.L.A.), July 2007.
Booklist, November 2006.
Keywords: Dreams -- Folklore; Folklore -- England; Dreams -- Folklore; Folklore -- England